Evaluation of a Novel Water Treatment Residual Nanoparticles as a Sorbent for Arsenic Removal. (7th December 2015) - Elkhatib, Elsayed; Mahdy, Ahmed; Sherif, Fatma; Hamadeen, Hala
Abstract : A novel sorbent, water treatment residual nanoparticles (nWTR), was synthesized and used to remove As(V) from water solutions. The kinetics and equilibrium of As(V) adsorption by nWTR were evaluated. The kinetic data for nWTR at 3 different pH values indicate that As(V) sorption is biphasic, is favored at low pH values, and followed the power function and first-order kinetics models fit. The results of the batch adsorption study showed that nWTR was effective in As(V) removal and its removal capability was 16 times higher than that of bulk WTR. Fourier transmission infrared (FTIR), SEM-EDX spectra, and As fractionation results indicate the crucial role of surface hydroxyl groups in As retention onto nWTR and the high capability of nWTR to immobilize As(V). The stability of As-nWTR surface complexes is suggested as less than 2% of adsorbed As(V) was released from nWTR after 4 consecutive desorption cycles.